Сетевые сообщества как объект социологического анализа - Коноплицкий, С. (Социология: теория, методы, маркетинг, 2004)
The article deals with sociological aspects of the net communities phenomenon. Necessity of studies on the communicative environment formed by the global computer net, stratification and other kinds of global interaction in the virtual space is discussed. There is a review of western and Russian works on the net societies. The author presents his idea of the cyber culture’s sense and context.